Kesadaran Keselamatan dan Kesehatan Kerja (K3): Kunci Keberhasilan Perusahaan Dalam Mengelola Risiko dan Produktivitas - Muhammad Abdul Ghofur; Muhammad Akbar Fandy Maulana; Yogi Dwi Muriyanto; Widjaya Tjipta Winarta; Denny Oktavina Radianto (Journal of Educational Innovation and Public Health, 2024)
Awareness of Occupational Safety and Health (OSH) has been recognized as a key factor in the success of companies in managing risks and improving productivity. This research investigates best practices to enhance OSH awareness in the workplace and its impact on company performance. Literature review identifies that comprehensive training programs, promotion of safety culture by management, active participation of employees in OSH-related decision-making, and implementation of incentive and reward systems are effective strategies to enhance OSH awareness. These practices provide employees with a deep understanding of potential workplace risks and the importance of safe behavior. Furthermore, the promotion of safety culture by management creates a work environment where safety is prioritized. Active employee participation in OSH decision-making strengthens a positive safety culture, while the implementation of incentive systems provides additional motivation for employees to adopt safe behaviors. By implementing these strategies in combination, companies can create a safer, healthier, and more productive work environment. This research provides valuable insights for stakeholders in developing effective OSH programs and improving overall company performance.